Frequency and Risk Factors of Anemia Among Adult Female Population of District Swat Khyber Pakhtunkhwa Pakistan - Naeemullah, Nadia Qazi, Bushra Ijaz, Nizam Muhammad Darwesh, Zahid Khan, Muhammad Ishtiaq, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Globally, anemia is the most common problem and affecting approximately 15 to 30% of adult population and the most common nutritional deficiency worldwide. According to WHO, anemia is more prevalent in children and women and too many etiological factors are responsible for its causation. The main objective was to assess the frequency and risk factors of anemia among the adult female population in District Swat Khyber Pakhtunkhwa Pakistan. Material and Methods: A descriptive cross sectional study was conducted from June to December 2021, in the district Swat, in which n=211 female individuals were selected through simple random sampling technique of age 18 years and above. Woman was termed as anemic if the HB level is below 10gm/ dl. A structured questionnaire was used to collect data and analyzed by SPSS version 19.0 and finally the results were presented in form of tables. Results: The results showed that 29.86% of adult female populations in the study populations were found anemic. 54.50% were married, 56.40% had monthly income less than 25000 PKR pm, 22.27% were housewives, 17.54% were illiterate, 21.33% had 3 or more children, and 15.17% were under-weight. Moreover, 63.98%, 43.60%, 21.33%, and 62.08% had history of iron supplements intake, had history of acute and chronic infections, had single food intake per day and less or equal to two time meat intake per week respectively. Conclusions: It was concluded that anemia among female adults had mild to moderate frequency and showed relationship with marital status, number of children, socioeconomic determinants, history of iron intake, acute and chronic diseases; and frequency of food and meat intake per day and week respectively, and thus health education and awareness services were needed to prevent and control anemia among the female adults.